Vps4A mediates the localization and exosome release of β-catenin to inhibit epithelial-mesenchymal transition in hepatocellular carcinoma. (10th August 2019) - Han, Qingfang; Lv, Lihong; Wei, Jinxing; Lei, Xin; Lin, Haoming; Li, Guolin; Cao, Jun; Xie, Jiyan; Yang, Weibang; Wu, Shaobin; You, Jia; Lu, Jing; et al.
Abstract: We previously reported that Vps4A acted as a tumor suppressor by influencing the microRNA profiles of exosomes and their parental cells in hepatocellular carcinoma (HCC). However, the underlying mechanism and if Vps4A contributes to sorting proteins into exosomes are not well known. Here, we performed mass spectrometry analysis of the immunoprecipitated Vps4A complex and confirmed that Vps4A was associated with β-catenin and CHMP4B. Through this interaction, Vps4A promoted the plasma membrane (PM) localization and exosome release of β-catenin. Silencing Vps4A or CHMP4B decreased the PM localization and exosome sorting of β-catenin. Vps4A overexpression decreased β-catenin signaling pathway and inhibited epithelial-mesenchymal transition (EMT) and motility of HCC cells. And, silencing Vps4A or CHMP4B promoted EMT in HCC. Furthermore, the expression of Vps4A was significantly related to that of several EMT markers in HCC tissues and the level of exosomal β-catenin in patients with metastatic HCC was significantly lower compared to that of control patients. In conclusion, through the interaction with CHMP4B and β-catenin, Vps4A regulates the PM localization and exosome sorting of β-catenin, consequently decreases β-catenin signaling, and thereby inhibits EMT and metastasis in HCC. Highlights: Vps4A immunoprecipitation experiments combined with mass spectrometry was performed. β-catenin is associated with Vps4A and CHMP4B. Vps4A regulates the localization of β-catenin. Vps4A contributes to the exosome sorting of β-catenin. Vps4A regulates epithelial-mesenchymal transition in hepatocellular carcinoma.